2007
DOI: 10.2114/jpa2.26.485
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control Adaptability to Floor Oscillation in the Elderly

Abstract: We established a method to evaluate postural control adaptability, applying it to 341 subjects, aged 18-29 years (young subjects) and 50-79 years, in order to investigate the influences of age and gender on adaptability. Subjects stood with eyes closed on a force plate fixed to a floor oscillator, which was sinusoidally oscillated in the anteroposterior direction with 0.5 Hz frequency and 2.5 cm amplitude. Five trials of 1-minute oscillation were conducted, with a short rest between trials. The mean speed of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
1
23
0
3
Order By: Relevance
“…To eliminate the influence of height on center of mass, we corrected the CoPy speed measurements for subject height and converted measurements into values per 100 cm. These formulas have been described in our previous study (Fujiwara et al, 2007). If subjects opened their eyes during table oscillation and again closed them, then the data from 10 seconds after they closed their eyes were used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To eliminate the influence of height on center of mass, we corrected the CoPy speed measurements for subject height and converted measurements into values per 100 cm. These formulas have been described in our previous study (Fujiwara et al, 2007). If subjects opened their eyes during table oscillation and again closed them, then the data from 10 seconds after they closed their eyes were used.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup is described in detail in our previous study (Fujiwara et al, 2007). In brief, a force platform (S110; Patella, Japan), which is composed of three load cells, was used to record CoPy fluctuations.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…In current approaches to motor learning, adaptation is viewed as a process in which prediction errors result in proportional changes in parameter estimates (Krakauer et al, 2006). More recently, studies have indicated that adaptation through motor learning can be applied to the human standing posture during balance perturbations (Fransson et al, 2007b;Fujiwara et al, 2007). As such, repeatedly perturbing balance could be one way of decreasing the number of falls in those at risk.…”
Section: Introductionmentioning
confidence: 99%